E-Government Assessment pada Kualitias Aplikasi Jogja Smart Service (JSS) di Kota Yogyakarta - Ramadhani Ramadhani; Eko Priyo Purnomo; Aulia Nur Kasiwi (Jurnal Pemerintahan dan Politik, 2020)
AbstractThe system of government in Indonesia has been quite dynamic and able to keep up with the times. This is evidenced by the electronics government (e-government) programme, with the use of Information and Communication Technology (ICT) in governance to improve performance and the relationship between government and other parties. Information is a very valuable commodity in the era of the industrial revolution 4.0 to be mastered to improve the competitiveness of an organisation. This is evident from the various initiatives the application of ICT, which is present in some local governments. Implementation of e-government in the governing of the city of Yogyakarta has the potential to improve the quality of public services, increasing transparency and accessibility of information. The purpose of this study is to want to assess how well the application Jogja Smart Service (JSS) as public service facilities in implementing smart city concept in the city of Yogyakarta. In this study using the e-government assessment to assess the application of JSS. The analytical method used in the assessment of applications JSS using the method of observation and direct observation on the application of JSS. The next stage of designing an assessment rubric used in the framework of e-government assessment, further testing using the application assessment frameworks assessment e-government. From the results of the study and application of the calculation of Jogja Smart Service (JSS) can be said to be very good to be a means of public service that is cheap, easy, and fast.Keywords : smart city, e-government, JSS, E-government assessmentAbstrakSistem pemerintahan di Indonesia sudah cukup dinamis dan mampu mengikuti perkembangan zaman. Hal ini dibuktikan dengan program E-Government, dengan penggunaan Teknologi Informasi dan Komunikasi (TIK) dalam tata kelola pemerintahan untuk meningkatkan kinerja dan hubungan antar pemerintah dengan pihak lain. Informasi merupakan komoditi yang sangat berharga di era revolusi industry 4.0 untuk dikuasai dalam rangka meningkatkan daya saing suatu organisasi. Hal ini terlihat dari berbagai inisiatif penerapan Teknologi Informasi dan Komunikasi (TIK), yang hadir dibeberapa Pemda. Penerapan E-Government pada penyelenggaraan pemerintahan di Kota Yogyakarta berpotensi meningkatkan kualitas pelayanan publik, meningkatkan transparansi dan aksesbilitas informasi. Tujuan dari penelitian ini ialah ingin menilai seberapa baik aplikasi Jogja Smart Service (JSS) sebagai fasilitas layanan publik dalam mengimplementasi konsep smart city di Kota Yogyakarta. Dalam penelitian ini menggunakan E-Government Assessment untuk menilai aplikasi Jogja Smart Service (JSS). Metode analisis yang digunakan dalam penilaian aplikasi Jogja Smart Service (JSS) menggunakan metode observasi dan pengamatan langsung pada aplikasi Jogja Smart Service (JSS). Tahap selanjutnya meranang rubrik penilaian yang digunakan pada kerangka kerja E-Government Assessment, selanjutnya melakukan pengujian penilaian aplikasi menggunakan kerangka kerja E-Government Assessment. Dari hasil kajian dan penghitungan aplikasi Jogja Smart Service (JSS) sudah bisa dikatakan sangat baik untuk menjadi sarana layanan public yang murah, mudah, dan cepat.Kata kunci : Smart City, E-Government, Jogja Smart Service (JSS), E-Government Assessment